Influence of neoadjuvant chemotherapy on resection of primary colorectal liver metastases: A propensity score analysis - Strowitzki, Moritz; Schmidt, Thomas; Keppler, Ulrich; Ritter, Alina; Klose, Johannes; Mihaljevic, André Leopold; Schneider, Martin; Büchler, Markus W.; Ulrich, Alexis (Journal of surgical oncology, 2017)
Background and Objectives There is ongoing debate about whether patients planned for liver resection of colorectal liver metastases (CRLM) benefit from neoadjuvant chemotherapy (NC). Therefore, we performed a retrospective survival analysis of patients with and without NC prior to surgery. Methods Data prospectively collected from 468 consecutive patients were analyzed in a retrospective design. We performed a survival analysis and added propensity score matching (PSM). Univariate and multivariate analysis was performed to determine independent prognostic risk factors. Results NC was performed in 145/468 patients. NC did not have a significant influence on overall survival (OS) either before or after PSM. Patients receiving NC showed increased complication rates, especially concerning non-surgical complications after primary resection (P = 0.025) of CRLM. Multivariate analysis before and after PSM revealed that the Memorial Sloan Kettering Cancer Center (MSKCC) score and CEA values are strong predictors for OS in patients with CRLM. Conclusions NC was not associated with increased OS in patients suffering from CRLM. Additionally, potentially harmful chemotherapy prior to surgery increases the risk of postoperative complications in these patients.
Gesehen am 20.04.2020